Violence : analysis, intervention, and prevention - Byrne, Sean, 1962-; Senehi, Jessica, 1959- (Research in international studies. Global and comparative studies series, 2012)
"In a world desperate to comprehend and address what appears to be an ever-enlarging explosion of violence, this book provides important insights into crucial contemporary issues, with violence providing the lens. Violence: Analysis, Intervention, and Prevention provides a multidisciplinary approach to the analysis and resolution of violent conflicts. In particular, the book discusses ecologies of violence, and micro-macro linkages at the local, national, and international levels as well as intervention and prevention processes critical to constructive conflict transformation. The causes of violence are complex and demand a deep multidimensional analysis if we are to fully understand its driving forces. Yet in the aftermath of such destruction there is hope in the resiliency, knowledge, and creativity of communities, organizations, leaders, and international agencies to transform the conditions that lead to such violence."--Provided by publisher.